A zenei teljesítményszorongás összefüggése a perfekcionizmussal és a szociális fóbiával - Dobos, Bianka; Pikó, Bettina (Magyar Pedagógia, 2017)
Music performance anxiety is a common problem that has a significant effect on musicians of different age groups. Although this topic emerges quite frequently in studies outside of Hungary, there are only a few that analyse Hungarian data. Our intention was to investigate the underlying sociodemographic and psychological factors related to music performance anxiety. The sample consisted of musicians (N=100; aged between 15 and 35 years) enrolled in secondary, postsecondary, or advanced/further music education. Descriptive statistics were used to compare data from the questionnaires. To explore the explanatory power of the predictors of music performance anxiety, we used hierarchical regression analysis. Our findings indicate that music performance anxiety is related to social phobia and perfectionism. The total scores for social phobia and perfectionism correlated significantly with music performance anxiety (K–MPAI); moreover, both variables proved to be positive predictors. Girls reported higher music performance anxiety and social anxiety, whereas there was no significant difference in the total scores for perfectionism. Models of hierarchical regression showed that gender, social phobia, and perfectionism significantly predicted K–MPAI. Four out of six subscales of perfectionism predicted music performance anxiety significantly, among which Parental Criticism and Doubts about Actions were positive, while Parental Criticism and Preference for Organization were negative predictors. Based on the data, there is a strong interrelationship between music performance anxiety, social anxiety, and certain aspects of perfectionism. It is likely that a social phobia may be responsible for some cases of stage fright. Our findings suggest that young musicians require greater support and acceptance from parents, teachers, and mental health workers.